Comparison of two selective media for the isolation of Listeria spp. from seafoods and their contact surfaces - Jeyasekaran, G; Karunasagar, Indrani; Karunasagar, I (Indian Journal of Fisheries, 2011)
Two commonly used selective media viz. PALCAM and LSAMM were comparedfor their efficiency in isolating Listeria spp. from seafoods and their contactsurfaces. The protocol followed for the isolation of Listeria spp. from seafoods andtheir contact surfaces was adopted from USDA - FSIS, USFDA and NGFISmethods. PALCAM was found to be better than LSAMM. About 92.8% isolatesof Listeria were recovered on PALCAM agar, while the recovery on LSAMM was42%. Though the isolation rates of Listeria spp. from smoked (70%), salted anddried seafoods (66.7%) was lower than that of the raw and frozen seafoods (100%),PALCAM agar was still the best media in isolating Listeria spp. from suchseafoods. LSAMM could not recover any isolates of Listeria spp. fromenvironmental samples and seawater. The recovery rate of Listeria spp. fromfrozen seafoods by LSAMM was also very low (12.5%).